Interactions between behavior function and psychotropic medication. Issue 1 (22nd September 2015) - Cox, Alison D.; Virues‐Ortega, Javier
Abstract : We reanalyzed published studies that reported functional analyses conducted in the presence and absence of medication. In Analysis 1, we assessed the overall effect of psychotropic medication on problem behavior. Medication had a reductive effect in 29 of the 37 sets of functional analyses reviewed. The magnitude of the effect was associated with the baseline level of responding according to a rate‐dependency function. Analysis 2 examined medication‐induced changes in behavior function. The introduction of medication was followed by the emergence of a new function (1), a change in functions (1), the subtraction of one function in multiply controlled problem behavior (2), and near‐zero levels of responding (6). Thus, in 4 of 37 cases reviewed, medication may have induced function‐specific changes in problem behavior. We discuss the implications of these findings for a closer collaboration between behavior analysts and prescribing professionals in the treatment of problem behavior.